Hepatoprotective Mechanisms Induced by Spinach Methanolic Extract in Rats with Hyperglycemia-An Immunohistochemical Analysis - Javier Flores-Estrada; Agustina Cano-Martínez; Álvaro Vargas-González; Vicente Castrejón-Téllez; Jorge Cornejo-Garrido; Martín Martínez-Rosas; Verónica Guarner-Lans; María Esther Rubio-Ruíz (MDPI AG, 2023)
Spinach methanolic extract (SME) has a hepatoprotective effect due to its polyphenolic antioxidants; however, its action in parenchymal (PQ) and non-parenchymal (nPQ) cells remains unknown. This study investigates the hepatoprotective effect of SME on streptozotocin-induced hyperglycemic rats (STZ), focusing on immunohistochemical analyses. Methods: The extract was prepared, and the total polyphenols and antioxidant activity were quantified. Adult male Wistar rats were divided into four groups (n = 8): normoglycemic rats (NG), STZ-induced hyperglycemic (STZ), STZ treated with 400 mg/kg SME (STZ-SME), and NG treated with SME (SME) for 12 weeks. Serum liver transaminases and lipid peroxidation levels in tissue were determined. The distribution pattern and relative levels of markers related to oxidative stress [reactive oxygen species (ROS), superoxide dismutase-1, catalase, and glutathione peroxidase-1], of cytoprotective molecules [nuclear NRF2 and heme oxygenase-1 (HO-1)], of inflammatory mediators [nuclear NF-κB, TNF-α], proliferation (PCNA), and of fibrogenesis markers [TGF-β, Smad2/3, MMP-9, and TIMP1] were evaluated. Results: SME had antioxidant capacity, and it lowered serum transaminase levels in STZ-SME compared to STZ. It reduced NOX4 staining, and lipid peroxidation levels were related to low formation of ROS. In STZ-SME, the immunostaining for antioxidant enzymes increased in nPQ cells compared to STZ. However, enzymes were also localized in extra and intracellular vesicles in STZ. Nuclear NRF2 staining and HO-1 expression in PQ and nPQ were higher in STZ-SME than in STZ. Inflammatory factors were decreased in STZ-SME and were related to the percentage decrease in NF-κB nuclear staining in nPQ cells. Similarly, TGF-β (in the sinusoids) and MMP-9 (in nPQ) were increased in the STZ-SME group compared to the other groups; however, staining for CTGF, TIMP1, and Smad2/3 was lower. Conclusions: SME treatment in hyperglycemic rats induced by STZ may have hepatoprotective properties due to its scavenger capacity and the regulation of differential expression of antioxidant enzymes between the PQ and nPQ cells, reducing inflammatory and fibrogenic biomarkers in liver tissue.